Prions en Chantant : Devotional Songs of the Trouvères. - Epstein, Marcia J. (Toronto medieval texts and translations., 1997)
An edition of largely anonymous trouvère devotional songs from the rich medieval French vernacular tradition, designed for both scholars and performers, from two late-13th-century manuscripts.